Study of Populus euphrafica OLfV. community in the margin of Karoon river - Mohsen Calagari; Karim Djavanshir; Mahmoud Zobeiry; Ali Reza Modir-Rahmati (تحقیقات جنگل و صنوبر ایران, 2000)
Populus euphratica Oliv. In Iran is distributed naturally in vast regions. But the largest area is located along the margins of the large rivers in Khuzistan province, such as Karkheh, Dez and some area in Maroon(nearly 20,000 ha). It is spread in the from of coppices covering at the large area, which are very important from the economical point of view and environmental purposes because of production of wood, animals fodder, protection and stabilization of the river border. Also it can be useful for the protection of the natural ecosystem and wildlife. P. euphratica in Khuzistan is adapted to arid and semi-arid regions. Also the dry period consider to Ombrothermic curves is between 7 and 8 month per year (late Feb. to late Oct). The mean annual rainfall is between 230-340 mm, and the mean annual temperature is between 23-25°C. Soil of the studied sites are alluvial which contribute from erosion of lime, marl and salty matters of Zagroos formations. Soil texture of upper horizons is sandy-loam and lower horizons change to loam. Electrical conductivity (EC) value is higher in south and western than north regions. The overall hydrological characteristics such as, meander, flood river and light texture of soil are the reasons for presence of P. euphratica communities in the natural regions. The number per hectare of stands was 357 and 329, the crown cover percentage of stands was 72.6 and 68.4. Also the mean annual diameter increament was 9.6 mm and 9.5 mm and the approximate age estimated 35 and 36 years.